O comportamento diurno e o bem-estar de vacas em sistema de confinamento compost barn - Pilatti, Jaqueline Agnes (2017)
The objective of this study was to evaluate the environment aspects, behavior and welfare of dairy cows in the compost bedded pack barns system in different seasons of the year. The research was conducted in a compost barn private property, at Dois Vizinhos city, Paraná state, Brazil. The research was carried out in two different periods in which the same variables were recorded. The warm months (September 2015 to February 2016) correspond to Chapter I and the cold months (April to June 2016), Chapter II. Crossbreed (Holstein x Jersey) and lactating cows were distributed into two treatments according to the order of lactation: primiparous and multiparous. The following microclimatic variables were measured: air, bed surface and bed interior temperature, air relative humidity and wind speed. To evaluate the thermoregulation of cows, the mean surface temperature (MST) and the respiratory rate (RR) were measured. The microclimatic variables and the animal thermoregulation were evaluated in specific hours. The diurnal behavior was evaluated between milking schedules from an etogram composed of different behaviors. Animal welfare was analyzed by means of hygiene scores and claudication. Regarding the statistical analysis, the microclimatic data were analyzed descriptively. For the thermoregulatory variables, a mixed model was fitted and, afterwards, they were submitted to analysis of variance and Tukey's test at a significance level of 5%. Animal behavior was analyzed using Bayesian inference, with a mixed effects model. Wilcoxon's non-parametric test was used to analyze the animal welfare data. Data processing and statistical analyzes were performed using statistical software R. The ambient air temperature in the compost bedded pack barns presented values above the external environment in all seasons. The internal temperature of bed varied from 36 to 36,7 °C during hot months and 23,6 to 25 °C in cold months. Regarding hot months there was a difference between hours and treatments, in relation to the RR and MST. The RR was 54 and 58 mov./min. for primiparous and multiparous, respectively. The behavior was influenced by property management, times of day and climatic conditions in all seasons. In hot months, breathing and butt behaviors differed between treatments and in cold months only walking behavior. The hygiene scores and claudication presented higher absolute frequency for scores 1 and 2, for all seasons. The results found in this research indicate the environment aspects related to thermal comfort were above the comfort zone of cattle in the afternoon in hot months and in cold months remained within the comfort zone. The behavior of the primiparous and multiparous cows was similar, presenting only difference in the activity of breath and push, and gait. Compost bedded pack barns system provided comfort conditions in relation to the aspects of the bed, allowing the cows to demonstrate a high level of animal welfare.